2006
DOI: 10.1080/09638280500494819
|View full text |Cite
|
Sign up to set email alerts
|

Stroke patients' experiences of return to work

Abstract: Purpose. The aim of this study was to describe the experience of return to work (RTW) after stroke from the patient's perspective.Method. Six patients who had their first ever stroke in 2001, were <65 years of age and were working at the time of their stroke were included. Information was obtained via an open-ended interview. The material was transcribed verbatim and analysed using Giorgi's empirical phenomenology.Results. Rehabilitation was perceived as primarily aimed at restoring bodily functions and a retu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

6
103
1

Year Published

2009
2009
2019
2019

Publication Types

Select...
4
2
1

Relationship

0
7

Authors

Journals

citations
Cited by 101 publications
(110 citation statements)
references
References 32 publications
6
103
1
Order By: Relevance
“…All participants placed extremely high value upon work and regarded the process of returning to work as a very significant step towards moving forwards with their lives, and recovering health, cognitive stimulation, social relationships and a 'normal' self-image. These findings resonate with the qualitative accounts given by people who have successfully returned to work following spinal cord injury, or stroke [17,21,22]. Ville and Ravaud [23] found that people with paraplegia valued work for providing opportunities for social integration above financial benefits.…”
Section: Discussionsupporting
confidence: 55%
See 2 more Smart Citations
“…All participants placed extremely high value upon work and regarded the process of returning to work as a very significant step towards moving forwards with their lives, and recovering health, cognitive stimulation, social relationships and a 'normal' self-image. These findings resonate with the qualitative accounts given by people who have successfully returned to work following spinal cord injury, or stroke [17,21,22]. Ville and Ravaud [23] found that people with paraplegia valued work for providing opportunities for social integration above financial benefits.…”
Section: Discussionsupporting
confidence: 55%
“…Not all studies have found prevalent concerns about stigma among those returning to work with a chronic condition. For example, Medin et al [17] found that people returning to work after a stroke welcomed the help and support of colleagues and managers, and were satisfied with a graded approach when returning to work. Yorkston et al [27] reported that people with multiple sclerosis seemed realistic about their physical impairments, developed proactive strategies to manage tasks at work, and welcomed appropriate support.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…This can be due to the significant work and social dysfunction experienced by most stroke survivors (Hommel et al 2009). Return to work can improve these outcomes by contributing to life satisfaction, wellbeing, self worth and social identity, at least partly through independence gained from income generation (Medin et al 2006). It is important to acknowledge that not all stroke survivors will RTW as a variety of factors such as the level of functional ability affect RTW (Vestling et al 2003).…”
Section: Introductionmentioning
confidence: 99%
“…It is important to acknowledge that not all stroke survivors will RTW as a variety of factors such as the level of functional ability affect RTW (Vestling et al 2003). Besides level of functional ability, high unemployment rate and poor socio economic status may also affect RTW as disability insurance and routine social security benefits may deter stroke survivors from returning to work (Treger et al 2007).The following seven broad categories of factors were reported to have an influence on RTW: age (Rollnik and Allman 2011); type of job (Noreau et al 2010); reasonable accommodation (Medin et al 2006); functional and cognitive ability (Jones et al 2006); the presence of co morbidities (Mars 2004); family support (Salter et al 2008); as well as community and work environmental barriers (World Health Organisation Report on Disability, 2011).…”
Section: Introductionmentioning
confidence: 99%